Learn more about

Refine search

Results (displaying matches 1-50 of 103) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
3969.b.35721.1 3969.b \(y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - 3x^2\) $E_6$ 2
7884.b.283824.1 7884.b \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 2
25913.a.25913.1 25913.a \(y^2 + (x^3 + x + 1)y = x^3 - x^2 - 2x\) $\mathrm{USp}(4)$ 3
41411.a.41411.1 41411.a \(y^2 + (x^3 + 1)y = -3x^4 + 7x^3 - 4x^2\) $\mathrm{USp}(4)$ 3
41663.b.41663.1 41663.b \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 4x^3 + 2x\) $\mathrm{USp}(4)$ 3
45413.a.45413.1 45413.a \(y^2 + (x^3 + x + 1)y = -x^5 + 2x^2 - 3x\) $\mathrm{USp}(4)$ 3
49507.a.49507.1 49507.a \(y^2 + (x^3 + 1)y = 2x^4 + 3x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 3
52498.a.104996.1 52498.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 - x + 1\) $\mathrm{USp}(4)$ 3
54983.a.54983.1 54983.a \(y^2 + y = x^6 - x^5 - 3x^4 + x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 3
57065.a.285325.1 57065.a \(y^2 + (x^3 + x + 1)y = x^4 - 4x^3 + x^2\) $\mathrm{USp}(4)$ 3
59107.a.59107.1 59107.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ 3
60617.a.60617.1 60617.a \(y^2 + (x^3 + x + 1)y = x^4 - 5x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
61127.a.61127.1 61127.a \(y^2 + (x^3 + x + 1)y = 2x^5 + 3x^4 - x^2\) $\mathrm{USp}(4)$ 3
61553.a.61553.1 61553.a \(y^2 + (x^3 + x + 1)y = -x^4 - 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
62563.a.62563.1 62563.a \(y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 3
63506.a.127012.1 63506.a \(y^2 + (x^3 + 1)y = 2x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 3
63707.a.445949.1 63707.a \(y^2 + (x^3 + x + 1)y = x^5 + x^3 + 6x^2 + 2x\) $\mathrm{USp}(4)$ 3
64237.a.64237.1 64237.a \(y^2 + (x^3 + x^2 + 1)y = x^3 - 3x\) $\mathrm{USp}(4)$ 3
67006.a.134012.1 67006.a \(y^2 + (x^3 + 1)y = 3x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 3
67203.c.604827.1 67203.c \(y^2 + (x^3 + x + 1)y = -x^4 - x^2 + 2\) $\mathrm{USp}(4)$ 3
71446.a.142892.1 71446.a \(y^2 + (x^3 + 1)y = 2x^5 - 4x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 3
79154.a.158308.1 79154.a \(y^2 + (x^3 + 1)y = 2x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 3
82413.a.247239.1 82413.a \(y^2 + (x^3 + x + 1)y = -x^5 + 2x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
83422.a.166844.1 83422.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 + x^2 - 7x + 6\) $\mathrm{USp}(4)$ 3
84685.a.423425.1 84685.a \(y^2 + (x^3 + x^2 + x)y = x^4 + 2x + 1\) $\mathrm{USp}(4)$ 3
85403.a.85403.1 85403.a \(y^2 + y = x^6 - x^5 + 2x^3 - x^2 - x\) $\mathrm{USp}(4)$ 3
86365.a.431825.1 86365.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + x^3 - 2x^2 + 2\) $\mathrm{USp}(4)$ 3
90963.d.818667.1 90963.d \(y^2 + (x^3 + x + 1)y = x^5 + 3x^4\) $\mathrm{USp}(4)$ 3
94533.a.283599.1 94533.a \(y^2 + y = x^6 - x^5 - 3x^4 + 3x^2 + 2x\) $\mathrm{USp}(4)$ 3
96677.a.676739.1 96677.a \(y^2 + (x^3 + x + 1)y = 2x^3 + 3x^2 + 3x + 2\) $\mathrm{USp}(4)$ 3
101679.a.305037.1 101679.a \(y^2 + (x^3 + x + 1)y = 2x^5 - x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 3
103767.a.311301.1 103767.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4 + x^3 - 3x\) $\mathrm{USp}(4)$ 3
104363.b.730541.1 104363.b \(y^2 + (x^3 + x + 1)y = x^5 + 5x^4 + x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
104482.a.208964.1 104482.a \(y^2 + (x^3 + 1)y = 2x^4 + x\) $\mathrm{USp}(4)$ 3
104996.a.419984.1 104996.a \(y^2 + y = x^6 - 2x^5 - 5x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 3
110848.b.221696.1 110848.b \(y^2 + x^3y = x^5 + x^4 - 3x^3 - 5x^2 + 2x + 4\) $\mathrm{USp}(4)$ 3
112529.a.112529.1 112529.a \(y^2 + (x^3 + 1)y = -3x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 3
113675.a.568375.1 113675.a \(y^2 + (x^3 + x + 1)y = -2x^5 + x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 3
115735.a.578675.1 115735.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 - 7x^2 - 3x + 6\) $\mathrm{USp}(4)$ 3
115784.a.231568.1 115784.a \(y^2 + x^3y = -4x^4 - 4x^3 + 3x^2 + 4x + 1\) $\mathrm{USp}(4)$ 3
117231.a.351693.1 117231.a \(y^2 + (x^3 + x + 1)y = -4x^4 - 5x^3 + x^2\) $\mathrm{USp}(4)$ 3
120436.a.481744.1 120436.a \(y^2 + x^3y = 6x^3 + 11x^2 + 6x + 1\) $\mathrm{USp}(4)$ 3
121994.a.243988.1 121994.a \(y^2 + (x + 1)y = x^6 - 3x^5 + 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
122084.a.244168.1 122084.a \(y^2 + (x^3 + x + 1)y = -x^5 + 3x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ 3
123171.a.369513.1 123171.a \(y^2 + (x^3 + x^2 + x)y = x^3 - 2x + 1\) $\mathrm{USp}(4)$ 3
125201.a.125201.1 125201.a \(y^2 + (x^3 + x + 1)y = 5x^5 + 8x^4 + 3x^3\) $\mathrm{USp}(4)$ 3
130105.b.650525.1 130105.b \(y^2 + x^3y = 4x^3 + 5x^2 - x - 2\) $\mathrm{USp}(4)$ 3
131074.a.262148.1 131074.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 2x + 2\) $\mathrm{USp}(4)$ 3
131169.b.393507.1 131169.b \(y^2 + (x^3 + x^2 + x)y = -2x^3 - x^2 + 2x + 1\) $\mathrm{USp}(4)$ 3
132206.b.264412.1 132206.b \(y^2 + (x^3 + 1)y = 2x^5 + 4x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
Next

Download all search results for